(3GaJJGM GdOYhI hGHJOGA GdOhdIs - (3GdbGVj GdfYeGf Hf Mjhf , CHh Mfjag GdfYeGf Hf eMeO Hf efUhQ Hf CMeO Hf Mjhf GdeUQj,J (B363 (3g` s ((3ShQJ s)
(3ChdgG (B:s
(3GdMeO ddg eDjO GdMb hfGUQ ChdjGFg hdh PcQfG cd EeGe efge dWGd GdcJGH HPcQge , hdcfG BKQfG ef Pdc PcQ CeQ GdOYhI HCQV GdeZQH Edi GdegOi s
(3BNQgG (B:s
(3jfHZi di Cf CNdi gPG GdcJGH ef (B( (3Cd (B) (3fcJ GdJi PcQJgG ajg , hPdc Ydi MSH eG TQWJ ef GdGNJUGQ ai Chdg , hHfjJ ef Pdc Ydjg hcGf HSWi EjGg ai GdeMQe SfI (B346 (3Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3HChdgG Cf eGdcgG UMM gPg GdCLRGA hCfgG fGbUIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B106s
Keywords: (3GdJGQjNs